2000
DOI: 10.1038/sj.onc.1203716
|View full text |Cite
|
Sign up to set email alerts
|

Cloning and expression of human B cell-specific transcription factor BACH2 mapped to chromosome 6q15

Abstract: The transcription factor Bach2, a member of the BTBbasic region leucine zipper (bZip) factor family, binds to a 12-O-tetradecanoylphorbol-13-acetate (TPA)-responsive element and the related Maf-recognition element (MARE) by forming homodimers or heterodimers with Maf-related transcription factors. Bach2 regulates transcription by binding to these elements. To understand the function in hematopoiesis, we isolated a cDNA clone for human Bach2 (BACH2) encoding a protein of 841 amino acid residues with a deduced a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
65
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 53 publications
4
65
0
Order By: Relevance
“…Although Bach2 was reported to be expressed specifically in B cells (11,12), we found that Bach2 was expressed in normal T cells at levels comparable with B cells. Peripheral T cells consist of mainly two populations: naive and memory T cells.…”
mentioning
confidence: 62%
“…Although Bach2 was reported to be expressed specifically in B cells (11,12), we found that Bach2 was expressed in normal T cells at levels comparable with B cells. Peripheral T cells consist of mainly two populations: naive and memory T cells.…”
mentioning
confidence: 62%
“…[57][58][59] In BL cell lines these deletions are consistently associated with loss of heterozygosity in the 6q25-27 region. 56 Genes possibly affected by 6q abnormalities include BACH2 (encoding for B-lineage specific transcription factor, a putative tumor suppressor gene), on 6q15, 60,61 and BLIMP1 (B-lymphocyte maturation promoting), on 6q21-q22.1. 62 In conclusion, our study identifies distinct secondary cytogenetic abnormalities in BL, some of which correlate with outcome in pediatric or adult patients.…”
Section: Discussionmentioning
confidence: 99%
“…The packaging cells and NIH3T3 cells were cultured in Dulbecco's modified Eagle's medium (Nissui) with 10% fetal bovine serum (JRH BioSciences), 100 units/ml penicillin, and 100 g/ml streptomycin (Invitrogen). Bach2-overexpressing and control Raji clones were described previously (31). The cells were treated with diethyl maleate (DEM) or H 2 O 2 (WAKO-jyunyaku) at the indicated concentrations.…”
Section: Methodsmentioning
confidence: 99%
“…Because Bach2 is expressed specifically in B-cells among hematopoietic cells (29), we were interested in whether Bach2 influences the sensitivity to oxidative stress among the B-lineage cells as well. Previously, we reported the establishment of Raji cell clones that overexpress human BACH2 (31). These clones seemed useful for examining the effects of Bach2 overexpression in B-cells because Raji cells do not express an endogenous BACH2 (31).…”
Section: Bach2-induced Cell Death Of B-lymphoma Cells-mentioning
confidence: 99%